1991
DOI: 10.1002/jbm.820251010
|View full text |Cite
|
Sign up to set email alerts
|

Bone bonding mechanism of β‐tricalcium phosphate

Abstract: It has been proposed that the formation of a surface apatite layer in vivo on surface active ceramics is an essential condition for chemical bonding between ceramics and bone tissue. To clarify the difference in bone-bonding mechanisms between surface active ceramics and bioresorbable ceramics, two experiments were performed using plates of dense beta-tricalcium phosphate (beta-TCP). First, plates of beta-TCP were implanted subcutaneously in rats for 8 weeks. Surface change due to bioresorption was observed wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
90
1

Year Published

1997
1997
2018
2018

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 200 publications
(101 citation statements)
references
References 19 publications
2
90
1
Order By: Relevance
“…In this context the present contribution aims not only to test the biocompatibility towards cells of bioceramic samples obtained by SPS, which is a technique that only recently has been employed for the production of bioglass and HA/bioglass composites, but also to further demonstrate that SBF assays should be considered as preliminary screening tests, since SBF is not able to mimic the complexity of a real physiological environment, which contains cells, proteins, specific trace elements, etc [39]. Cytotoxicity tests, based on in vitro cell culture assays, are crucial in order to confirm the findings from the bioactivity evaluation with SBF, which has been reported in the literature to lead both to false negative and false positive results [40][41][42]. In this context, probably the most striking case is that of β-Tricalcium Phosphate: despite its high bone-bonding ability in vivo, it does not always induce the formation of hydroxyapatite in SBF [39].…”
Section: Resultsmentioning
confidence: 99%
“…In this context the present contribution aims not only to test the biocompatibility towards cells of bioceramic samples obtained by SPS, which is a technique that only recently has been employed for the production of bioglass and HA/bioglass composites, but also to further demonstrate that SBF assays should be considered as preliminary screening tests, since SBF is not able to mimic the complexity of a real physiological environment, which contains cells, proteins, specific trace elements, etc [39]. Cytotoxicity tests, based on in vitro cell culture assays, are crucial in order to confirm the findings from the bioactivity evaluation with SBF, which has been reported in the literature to lead both to false negative and false positive results [40][41][42]. In this context, probably the most striking case is that of β-Tricalcium Phosphate: despite its high bone-bonding ability in vivo, it does not always induce the formation of hydroxyapatite in SBF [39].…”
Section: Resultsmentioning
confidence: 99%
“…13 Neo and Kotani et al showed that b-TCP directly bonded to bone intervening no apatite layer by in vivo tests. 4,14,15 On the other hand, Daculsi et al reported formation of carbonate apatite layer in the vicinity of implanted b-TCP. 16 However, connectivity of b-TCP with host bone was reported to be strong in general and attributed to rough surface due to degradation of implanted b-TCP.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the volume percentage of the total porosity should be higher than 60% [7]. Besides the requirement for a specific macroporosity of the ceramic scaffold, a certain percentage of microporosity is important for osteogenesis and the anchoring of the implant to sur rounding bone tissue [14]. Therefore, several techniques were developed to integrate the desired porous structure into calcium phosphate scaffolds [15][16][17][18][19][20][21][22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%